2021
DOI: 10.1021/acs.energyfuels.1c02702
|View full text |Cite
|
Sign up to set email alerts
|

Supercritical High-Pressure Methane Adsorption on the Lower Cambrian Shuijingtuo Shale in the Huangling Anticline Area, South China: Adsorption Behavior, Storage Characteristics, and Geological Implications

Abstract: Supercritical high-pressure methane (CH 4 ) adsorption analysis was performed to investigate the gas adsorption behavior and storage capacities of the Lower Cambrian Shuijingtuo Shale in the Huangling anticline area, South China. The paraboliclike shapes of the excess isotherms are ascribed to the relative increasing rate of the adsorbed gas density (∂ρ ads /∂ P ) and free gas density (∂ρ free /∂ P ). The maximum value occurs where the ∂ρ ads /∂ P value is equal to that of the ∂ρ free /∂ P value. The adsorptio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 67 publications
0
8
0
Order By: Relevance
“…As shown in Figure 6, we obtained the pore-volume distributions for six samples by the Barrett−Joyner−Halenda (BJH) analysis. 57,58 The results show that the main pore-size distributions of the six samples range from 1 to 100 nm, and the pore-volume change rate decreases rapidly with the increasing pore size. As the pore size increases to 10 nm, the pore-volume change rate decreases below 0.001.…”
Section: Resultsmentioning
confidence: 99%
“…As shown in Figure 6, we obtained the pore-volume distributions for six samples by the Barrett−Joyner−Halenda (BJH) analysis. 57,58 The results show that the main pore-size distributions of the six samples range from 1 to 100 nm, and the pore-volume change rate decreases rapidly with the increasing pore size. As the pore size increases to 10 nm, the pore-volume change rate decreases below 0.001.…”
Section: Resultsmentioning
confidence: 99%
“…Based on free CH 4 density obtained from the NIST package [31] and the above calculated excess CH 4 adsorption amounts, the relationship between the buried depth and GIP was established and shown in Figure 8. It is worth noting that, here, the GIP calculation for the Shahezi and Yingcheng formations should be overestimated because the CH 4 adsorption isotherms were actually conducted under dry conditions [12][13][14]. The estimated GIP values of HS1-1 (1.388 m 3 /t) and S2-1 (3.307 m 3 /t) at sampling depth indicated favorable shale gas resources potential, especially in shales of the Yingcheng Formation.…”
Section: Evaluations Of Gip: Implications For Shale Gas Resourcesmentioning
confidence: 93%
“…The GIP calculation referred to the maximum amount of gas stored in shale reservoirs [12,13], which was the sum of the free gas content and adsorbed gas content [14]. The adsorbed gas amount was obtained based on excess adsorption data, while the free gas amount was calculated from the pore volume and free gas density under geological temperature and pressure [12,14]. The modified and simple equation was developed by Tian et al [14] to calculate GIP, as shown in Equation ( 4):…”
Section: Evaluations Of Gip: Implications For Shale Gas Resourcesmentioning
confidence: 99%
See 1 more Smart Citation
“…Excess adsorption isotherms were fitted by the supercritical Dubinin–Radushkevich (SDR) model, and the adsorbed gas density can be obtained. The calculations of the absolute amount of methane adsorption were described by Wei et al…”
Section: Samples’ Geological Background and Methodologymentioning
confidence: 99%